Tube Bending Machine for Home Industry Scale - Lestari, Nidia; Kurniawan, Stephanus Danny; Yudhanto, Bagas (Institut Teknologi Dirgantara Adisutjipto, 2018)
Tube bending is a general term for the process of forming metals used to form pipes or tubes permanently. By utilizing plastic deformation, straight objects are bent to form arches. Metal pipes in the form of arches can be used as a connection to machine construction, circular ladders, bicycle frames, motor frames, furniture, musical instruments. To improve time and energy efficiency in the bending process, a roll bending machine is designed. This machine is also expected to meet the needs of buckling pipes so that it can be used as a business field by the community. This machine can bend pipes 3/4 inch to 1 inch with a thickness of 1 mm.